ANALISIS PENGARUH FUN AT WORK TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) DENGAN KEPUASAN KERJA DAN WORK ENGAGEMENT SEBAGAI VARIABEL INTERVENING (Studi Pada PT Djarum di Kudus) - Matofani, Niken; Djastuti, Indi (Diponegoro Journal of Management, 2016)
The aim of this study is to analyze the influence of the perceived presence of fun at work toward organizational citizenship behavior (OCB) with job satisfaction and work engagement as intervening variable. This study using samples from employers of PT Djarum in Kudus. Samples taken by are 125 respondents using Non-Probability Sampling technique where not all members of tthe population in the same position have the opportunity to be selected into the sample.  The analyzed data comes from distributed questionnaires to employees, then its analzed using confirmatory  factor  analysis  and  regression  weight  with  AMOS  22.The  result  of  Structural Equation Model analysis indicated that fun at work have direct and indirect impact on organizational citizenship behavior (OCB). Implication and suggestion for further research also discussed.